OUTDOORS BATCH CULTIVATION OF MARINE MICROALGAE Nannochloropsis sp USING PARALLEL GLASS TUBULAR PHOTOBIOREACTOR - Astuti, J.T -; Sriwuryandari, L. -; Priantoro, E.A -; Sembiring, T - (Direktorat Sumber Daya Akademik dan Perpustakaan, 2012)
ABSTRACTMicroalgae Nannochloropsis sp is autotrophic organism that can utilize atmospheric CO2 and sunlightfor growth via photosynthesis. It is potential sources for biodiesel due to its high lipid content. Formass production, two basic designs of photo-bioreactor are available, i.e. open and enclosed systems.Study was conducted to investigate the growth performance of Nannochloropsis sp in outdoor batchculture system using Parallel Enclosed Glass-Tubular Photo-bioreactor (PBR) for 18 days withmodified f/2 medium. Nutrient N-P was calculated based on the empiric structure of microalgae cell(C1O0.48H1.83N0.11P0.01) with target of biomass yield was 1gL-1. Temperature, pH, Optical Density (OD),Dry Cell Weight (DCW), population, lipid content, and fatty acid were observed. Data showed thattemperature fluctuated between 22oC and 35oC, pH was stable at 7.0-7.5, OD increased from 0.134 to0.878, DCW increased 39 times higher than its initial value. At the 18th day, the cell diameter variedin range of 1-9 μm, cell weight increased 5.3 times (3.5 to 18.4 pg.cell-1), and lipid content is 35.71%.Fatty acid was composed by saturated fatty acids (92.39%) that covered of lauric (20.30%), myristic(12.69%), palmitic (50.05%), and stearic (9.35%) that was suitable for biodiesel. Unsaturated fatty acidwas performed by oleic acid (3.49%).Key words: CO2 mitigation, biodiesel, Nannochloropsis sp, photo bioreactor